Contract for Public Procurement in Terms of Private Law - O. L. Zaitsev; S. V. Yasechko (Law and Safety)
The authors have analyzed the way of the origin and consolidation of the public procurement procedure in the Ukrainian national law from 1993 till the present day. That allowed us to determine the main conditions of public procurement, which have not changed during the whole period of existence of the independent legal system of Ukraine, and to critically evaluate them. Namely, the basis for payment is a report on the results of public procurement during the procurement of goods, works or services, and the cost of procurement should have been equal to or have exceeded the amount of UAH 200,000.